Strategizing knowledge management in the Malaysian Armed Forces : towards knowledge-centric organization / Ismail Manuri and Raja Abdullah Yaacob - Manuri, Ismail; Yaacob, Raja Abdullah (Faculty of Information Management, 2011)
Military knowledge management (KM) is about the processes and techniques used to swiftly transfer experience and provide a common understanding from an experienced soldier to an inexperienced soldier. As an integral part of the Malaysian Armed Forces (MAF) transformation to achieve Future Force, the KM strategy will play a valuable role in leveraging existing knowledge and converting new knowledge into action. A study on military officers of the MAF attitudes towards' KM applications was conducted to show the importance of KM in the military environment. Focus of the study is to examine the attitudes of MAF personnel toward KM key drivers, which include the knowledge creation, processes, applications, and technology. The findings of the study may be used as the basis to develop a KM implementation strategy in the MAF which should focussed on the tenet of people, process, and technology. The results of the study indicated that the KM key drivers that include knowledge creation, KM processes, KM application and technology were perceived as key elements in the military organization. In order to develop KM implementation strategy successfully, the MAF needs to focus on factors that include people, KM processes, and infostructure.